Listening to locals on payments for environmental services - Petheram, L.; Campbell, Bruce M. (Elsevier, 2010)
Payments for Environmental Services (PES) is gaining recognition worldwide as a serious option for conservation of ecosystems, as well as potentially improving the livelihoods of people providing environmental services. However, little attention has been paid to research on views of local people in their potential roles as service providers. In this research we explore perspectives of poor people living in a National Park in Vietnam, where introduction of PES is being considered. In-depth interviews and workshops were conducted – with strong emphasis on the use of visual techniques, to help facilitate learning processes and provide insight into local perspectives. From the research, two models were developed to indicate general factors that influence the likelihood of people adopting, and adhering to, PES schemes. We suggest these models can be used to guide the design of PES. Our findings also reveal three main requirements important in design of pro-poor PES: (1) Thorough scoping studies for ensuring that schemes are based on sound understanding of potential providers' perspectives and context. (2) Such studies should emphasise qualitative research and draw on participatory tools, to facilitate open dialogue and co-learning by researchers and participants. (3) Policy makers should consider designing hybridized schemes, i.e., in which PES concepts are combined with integrated conservation and development.